UJI ANTIMITOSIS EKSTRAK ETANOL BUAH MERAH (Pandanus conoideus Lam) DENGAN METODE PENGHAMBATAN PEMBELAHAN SEL TELUR Tripneustes gratilla Linn TERFERTILISASI - Sitti Amirah; Heriyanto Beddu (Fakultas Farmasi UMI, 2012)
The research concerning antimitotic assay of ”Buah Merah” (Pandanus conoideus Lam) ethanol extract using sea urchin Tripneustes gratilla Linn eggs cleavage inhibition method had been conducted. The aim of this study was to determine the antimitotic effect of buahMerah ethanol extract in to inhibit cell cleavage of fertilized sea urchin eggs. Buah Merah ethanol extract was made in to 5 concentration there was 0,001 µg/ml, 0,01 µg/ml, 0,1 µg/ml, 1 µg/ml and 10 µg/ml with vincristine as the compared. Quantivication of cell cleavage was performed visually under the light microscopy by counting the number of cleaveaged and non cleaveaged embryos after an incubation time of ± 2 hours. If 80-100% inhibition of cleavage (IC80-100) occurs at ≤ 16 mg/ml, the compound is considered to be active as antimitotic. The result of this research showed that IC80 value of ”BuahMerah” ethanol extract was 0,026 mg/ml. According to the value ethanol extract was categorized active as antimitotic, although their potency lower than vincristin which can inhibit 80 % of fertilized sea urchin eggs at 2,789x10-4 mg/ml.Key words: Pandanus conoideus Lam, Antimitotic, Tripneustes gratilla Linn.